Gamification Based on Android to Improve Comprehension Civics for Deaf Student - Aisyah Ayu Mustikasari; Munawir Yusuf; Triana Rejekiningsih (International Journal of Elementary Education, 2023)
The problems that occur in the learning process for class III SLB B or deaf students originate from how the teacher conveys the material and the characteristics of the students. Teachers still teach in a simple method, so students get bored quickly. In the learning process, media is needed that prioritizes visuals to make it easier for students to capture the material presented by the teacher. This study aims to develop android-based gamification learning media on Civics theme 8 material. This research uses the Research and Development (RnD) method using the ADDIE approach. The participants in this study were 20 students of class III SLB B. The process of collecting data with interviews, questionnaires, and observation. At the same time, the instruments used are questionnaires and tests. Data analysis technique using SPSS with independent t-test. The result is that Android-based gamification media can be used in the learning process. In the experimental class, the average post-test score is 9.10, while in the control class is 8.00. Based on these values, the use of Android-based gamification learning media in the experimental class increased students' understanding of Civics compared to the control class, which did not use gamification learning media. Thus, gamification has a positive influence on increasing student understanding.